PENGARUH KARAKTERISTIK AUDIT TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Barang Manufaktur yang Terdaftar di BEI tahun 2023-2024) - Marsha Indra Ayu Ivana; Herry Laksito (Diponegoro Journal of Accounting, 2026)
The purpose of this study is to explore the impact of audit characteristics on Tax Avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2023 and 2024. In this study, audit characteristics are analyzed through Audit Fees, audit duration, and audit quality as independent variables, while Tax Avoidance is examined through the Effective Tax Rate (ETR) as the influencing variable. The data used are secondary data obtained from the financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange. The sample was selected using a purposive sampling method based on predetermined criteria. The study sample consisted of 20 manufacturing companies during the 2023–2024 period, resulting in 40 observations. The analytical method used was multiple linear regression analysis with the assistance of IBM SPSS Statistics 26. The study results indicate that Audit Fees have a significant negative impact on Tax Avoidance. Although audit duration also shows a negative relationship with Tax Avoidance, the effect is not significant and therefore does not influence Tax Avoidance. On the other hand, audit quality has a significant negative impact on Tax Avoidance. The analysis simultaneously shows that Audit Fees, audit duration, and audit quality all contribute to Tax Avoidance.